Conducting polymer-based textile materials - Che Roslan, Nazreen; Aizamddin, Muhammad Faiz; Ahmad Ruzaidi, Dania Adila; Ayub, Ayu Natasha; Asri, Nurul Ain Najihah; Jani, Nur Aimi; Shafiee, Saiful Arifin; Mahat, Mohd Muzamir (Woodhead Publishing, 2022)
The new age of wearable technology has popularized the field of smart textiles among researchers. In essence, smart textiles are functional textiles with applications in various industries such as healthcare, sports, automotive, semiconductor, and military. The convergence of textiles and electronics (e-textiles) united electronic functionalities without compromising the comfort of conventional textiles. E-textiles are also commonly known for their flexibility, wearability, breathability, and lightweight. Due to their favorable characteristics, e-textiles have made their way into a variety of applications such as biosensors, wearable antennas, artificial muscles, thermoelectric clothing, etc. Electrical conductivity can be introduced into the textile by embedding conducting materials through melt-spinning or coating techniques. However, the rigidity of conducting materials such as metal may compromise the mechanical properties of the textile. This inherent disadvantage with common conducting material presents an opportunity to evaluate the feasibility of conducting polymers (CPs) in e-textiles. This type of polymer combines the mechanical traits of plastics with the electrical properties that are typical of metals. At the moment, CPs that are frequently studied are polypyrrole, polyaniline, polythiophene, and its derivative, poly(3,4-ethylyene dioxythiophene). However, some challenges must be considered while designing conductive textiles, such as the stability of the conductive materials in their environment, washability of the textile, viability in industrial manufacturing, etc. In this chapter, we will go through an overview of the various aspects of conductive textile, followed by the finer details on its fabrication techniques, challenges, and potential application. Finally, we will discuss future directions in the research to develop an ideal CP-based smart textile.